KRITIK BAHAYA SAMPAH PLASTIK DALAM MURAL “SILENT” DI KULIDAN KITCHEN SPACE KARYA DJAMUR KOMUNITAS (ANALISIS SEMIOTIKA CHARLES SANDERS PIERCE) - Ganeshwara, I Komang Bayu; Purnawan, Ni Luh Ramaswati; Joni, I Dewa Ayu Sugiarica (E-Jurnal Medium, 2023)
Djamur Komunitas is an art community that based in Bali established in 2007. Their members spread in almost all the districts in Bali. Most of their artworks speak about criticism, especially for environmental issues. One of their art work, titled “Silent”, can be found in Kulidan Kitchen Space. That mural can be seen in an area on its backyard wall. Mural “Silent” drew in an event named TrashStock Festival 2017. This study used descriptive qualitative research with a constructivist paradigm. The data collecting used some techniques, such as interview, observation, documentation, literature study and analysis of symbols. The result shows that the mural “Silent” contains messages for Balinese people to be more aware and more careful about environmental sustainability, so Bali’s nature is not damaged due to the construction of tourism facilities. This is reinforced by a statement from the painter directly who stated that each symbol in the “Silent” mural has its own meaning, which serves to convey the criticism. Keywords: Representation, Mural, Community Djamur, Plastic Waste.